2018
DOI: 10.1111/bcp.13790
|View full text |Cite
|
Sign up to set email alerts
|

Self‐poisoning with 60 tablets of Apixaban, a pharmacokinetics case report

Abstract: A 67‐year‐old man was admitted to the emergency department about 5 h after deliberate self‐poisoning with 300 mg of Apixaban. The clinical examination did not show any organ dysfunctions or haemorrhagic signs, and the patient's life was not in danger. The first analysis, upon admission, showed a concentration of 2655 μg l−1 of Apixaban. The Cmax was observed 17 h after the intake (3654 μg l−1), about four times the classical Tmax value (median [range]: 4 h [2–4]). The Apixaban was then eliminated following a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Apixaban blood concentration increased up to a high level of 1712 μg/L at H + 6 after ingesting 40 mg of apixaban (3.1 mg/Kg). Cmax was consistent with data in adults overdose (between 1000 and 2750 μg/L after ingesting 2 to 5 mg/kg of apixaban) [ 5 , 6 ].…”
Section: Discussion/conclusionsupporting
confidence: 87%
See 2 more Smart Citations
“…Apixaban blood concentration increased up to a high level of 1712 μg/L at H + 6 after ingesting 40 mg of apixaban (3.1 mg/Kg). Cmax was consistent with data in adults overdose (between 1000 and 2750 μg/L after ingesting 2 to 5 mg/kg of apixaban) [ 5 , 6 ].…”
Section: Discussion/conclusionsupporting
confidence: 87%
“…As previously reported, the apixaban plasma concentration vs. time profile exhibited a multiphasic elimination profile, with an initial rapid decline followed by a more gradual terminal phase [ 4 ]. Apixaban was eliminated with a terminal half-life of 8.2 h. The half-life described in adults overdose was between 6 h and 15 h depending on the patient and other co-administered drugs [ 6 9 ]. The rapid elimination may explain the absence of bleeding despite high concentrations.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overdose resulting from DOAC self‐ingestion has been poorly reported, mostly as single cases, limited series and PCC reports, representing ~100 cases, with serum/plasma concentration assessment in <20 cases (Table 3). 12–35 Overall, suicidal ingestion does not seem to result in notable bleeding despite high‐ingested amounts and high peak plasma concentrations in most patients. Of note, peak DOAC concentrations in patients included in clinical trials evaluating DOAC for stroke prevention in atrial fibrillation or venous thromboembolism treatment (ie at regular doses) showed a wide inter‐individual variability 3,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 29 additional cases mostly involving intentional exposure to dabigatran ( n = 15), rivaroxaban ( n = 8) and apixaban ( n = 6) were published (Table 3). 12–35 Only 10 of these 29 cases presented bleeding. A 53‐year‐old man who co‐ingested 200 mg apixaban presented minor oozing from his femoral venous line insertion site, easily controlled with direct pressure and prothrombin complex concentrate 13 .…”
Section: Discussionmentioning
confidence: 99%